Utilization of Augmented Reality E-Pregnant As Educational Media For Improving Prevention Behavior Caries in Pregnant Mothers - Natalia Natalia; Lanny Sunarjo Sunarjo; Masrifan Djamil (Jurnal Health Sains, 2023)
Pregnant women are one of the groups that are susceptible to dental and oral diseases. This is because during pregnancy there is an increase in the amount of the hormones estrogen and progesterone so that the acidity in the mouth increases which can increase the risk of caries. This condition causes babies to be born with low weight (LBW) and premature due to lack of nutrition. Thus, to reduce the magnitude of the incidence of caries in pregnant women, a learning media is needed. The technology in education that is currently developing is augmented reality. To produce an augmented reality application model of E-Pregnant as an appropriate and effective educational media in improving the behavior of pregnant women towards the prevention of dental caries and decreasing the OHIS score. The type of research used is Research and Development and the research design used is Quasy experiment Pretest-Posttest group design. Variables in this study: Knowledge, attitudes, actions and OHIS scores carried out for 21 days by opening the application 3 times a week and uploading photos 2 times a day. The research subjects were in 2 groups: 24 interventions using an e-pregnant caries application and 24 controls using a pocket book. The Augmented Reality E-Pregnant Caries model is feasible as a media for dental caries prevention education with 90% expert validation results. The results of the unpaired test stated that the effective application of increasing knowledge (Δ3.58), attitude (Δ15.63), action (Δ5.75), and also reduced the OHIS score (Δ0.60) compared to the control group. The Augmented Reality E-Pregnant Caries model is proven to be feasible as a caries prevention, education media and its application is effective as an effort to improve caries prevention behavior and reduce OHIS scores in pregnant women compared to the control group.